Immunological Profile of Serum Antibodies, Multiplex Cytokines, and Complement Proteins in Cystic Echinococcosis Patients - Faleeha Habeeb Hussien (Medical Journal of Babylon, 2023)
Background: Cystic echinococcosis (CE) is a zoonotic parasite disease that affects people globally and causes cysts to develop in internal organs. Objectives: This study aimed to examine the effects of E. granulosus infection on the level of some immunological cytokines such as IL-2, IL-4, and IL-6 and the level of IgM and IgG antibodies as well as to investigate the effects of hydatid cysts disease on complement proteins. Materials and Methods: This case–control study was carried out on 46 individuals whose ages ranged between 20 and 70. The study extended from September 2021 to May 2022. ﻿Forty-six blood samples were collected from patients infected with hydatidosis and 10 blood samples from non-infected as a control group. The blood samples were used to obtain the desired sera for immunological detection: immunoglobulins (IgM and IgG); interleukins (IL-2, IL-4, and IL-6) by using enzyme-linked immunosorbent assay and complement proteins (by using radial immnodiffusion plate). Results: The level of anti-echinococcosis IgM (304.7 ± 73.4 mg/dL) was higher in infected than uninfected persons (161.8 ± 14.2 mg/dL). Anti-echinococcosis IgG level in an infected individual (1587.3 ± 449.4 mg/dL) was higher when compared with control (1136 ± 25.4 mg/dL). The highest number of cases (19, 41.30%) was observed in age 41–50 years, followed by the age 31–40 years (11, 17.18%). The results showed a high increase in the incidence of infection with hydatid cyst among men (58.69%) in comparison to women (41.30%). The patients most at risk are those living in intimate association with animals’ environments. Three cytokines including (IL-6, IL-4, and IL-2) were significantly elevated (474.8 ± 116, 6.86 ± 0.6, and 7.01 ± 2.89 pg/mL) in patients with hydatidosis disease in comparison with the normal controls (118.4 ± 14.3, 6.11 ± 0.3, and 4.54 ± 0.4 pg/mL). Examining the complement protein production, we found that C3 and C4 were significantly higher (159.5 ± 51.6 and 36.15 ± 6.13 mg/dL) in patients with hydatidosis than those of controls (117.7 ± 8.1 and 26.4 ± 3.1). Conclusions: Our findings provide information on the effects of E. granulosis parasite on the profile of serum antibodies, multiplex cytokines, and complement proteins in cystic echinococcosis patients.